2020
DOI: 10.1101/2020.10.14.339259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The claustrum-medial prefrontal cortex network controls attentional set-shifting

Abstract: In various mental disorders, dysfunction of the prefrontal cortex contributes to cognitive deficits. Here we studied how the claustrum (CLA), a nucleus sharing reciprocal connections with the cortex, may participate in these cognitive impairments. We show that specific ensembles of CLA and of medial prefrontal cortex (mPFC) neurons are activated during a task requiring cognitive control such as attentional set-shifting, i.e. the ability to shift attention towards newly relevant stimulus-reward associations whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 98 publications
8
61
1
Order By: Relevance
“…More recent studies have associated the claustrum with many diverse functional and cognitive roles including sensory change detection (Remedios et al, 2014), top-down action control (White et al, 2020(White et al, , 2018, behavioral impulse control (Liu et al, 2019), navigation and spatial location coding (Jankowski and O'Mara, 2015), slow wave sleep (Narikiyo et al, 2020;Norimoto et al, 2020), attentional set shifting (Fodoulian et al, 2019), distractor suppression . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have associated the claustrum with many diverse functional and cognitive roles including sensory change detection (Remedios et al, 2014), top-down action control (White et al, 2020(White et al, , 2018, behavioral impulse control (Liu et al, 2019), navigation and spatial location coding (Jankowski and O'Mara, 2015), slow wave sleep (Narikiyo et al, 2020;Norimoto et al, 2020), attentional set shifting (Fodoulian et al, 2019), distractor suppression . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have associated the claustrum with many diverse functional and cognitive roles including sensory change detection (Remedios et al, 2014), top-down action control (White et al, 2020, 2018), behavioral impulse control (Liu et al, 2019), navigation and spatial location coding (Jankowski and O’Mara, 2015), slow wave sleep (Narikiyo et al, 2020; Norimoto et al, 2020), attentional set shifting (Fodoulian et al, 2019), distractor suppression (Atlan et al, 2018), associative learning (Reus-garcía et al, 2020) and contextual association of reward (Terem et al, 2020). The diversity of functional properties measured in the claustrum could reflect spatially separate domains or cell types with distinct inputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our answer begins with the simplified network, consisting of four pathways, shown in Figure 2A. Within a claustrocortical loop (Pathway 1), the claustrum may exert net inhibitory effects through feed-forward inhibition (FFI) that is mediated by claustrum excitation of local cortical interneurons (Ptito and Lassonde, 1981;Tsumoto and Suda, 1982;Salerno et al, 1984;Jackson et al, 2018;Narikiyo et al, 2020) and/or possibly net excitation, as suggested by more recent evidence (Fodoulian et al, 2020). This loop also includes excitatory monosynaptic input that claustral projection neurons and interneurons receive from various cortical regions (Kim et al, 2016;White and Mathur, 2018b;White et al, 2018;Chia et al, 2020); whether this combined input exerts a net inhibitory or excitatory effect on the claustrum remains unknown.…”
Section: A Unified Picture Of Neuromodulator Control Of the Claustrummentioning
confidence: 96%
“…Recent findings have converged on a critical role for the claustrum in attention (Atlan et al, 2018;Fodoulian et al, 2020).…”
Section: Cholinergic Modulation As a Permissive Gate For The Claustrum In Attention And Sleepmentioning
confidence: 99%